Pengaruh Kemudahan Penggunaan, Pengalaman Pengguna Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Penggunaan Aplikasi Dompet Digital (E-Wallet) di Kalangan Mahasiswa Universitas Buddhi Dharma - Aldi Samara; Metta Susanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to determine the effect of Ease of Use, Customer Satisfaction, and User Experience on Customer Loyalty for Buddhi Dharma University students who are registered for the 2022 period either simultaneously or partially. The sample in this study was 105 students enrolled at Buddhi Dharma University for the 2022 period. The method used was mixed methods. This research is a research step by combining two forms of research that have existed before, namely qualitative research and quantitative research. The results of the R - Square test give a test value of 0.505 for the variable Firm Value which can be concluded that the variable Ease of Use, Customer Satisfaction, and Experience Users are simultaneously able to explain the variable Customer Loyalty of 50.50%. This shows that the ease of using the e-wallet application, the level of satisfaction with the application features provided and the ability to create an experience using the application can substantially affect Customer Loyalty. While the rest is influenced by other factors outside of this study such as promos, obligation and or responsibility to pay bills, the need for pulses and or quotas, and some others. Testing the variable Ease of Use with Customer Loyalty is not significant with a T-statistic of 0.907 (<1.9828), so the research hypothesis of Ease of Use with Customer Loyalty is rejected. Testing the variable Customer Satisfaction with Customer Loyalty is significant with a T-statistic of 2.905 (> 1.9828), so the research hypothesis of Customer Satisfaction on Customer Loyalty is accepted. Testing the variable User Experience with Customer Loyalty is significant with a T-statistic of 3.072 (> 1.9828), so the research hypothesis of User Experience on Customer Loyalty is accepted.